Clinicians' perceptions of domestic violence routine screening in public dentistry - Ms Cecilia Correy; Mrs Natalia Uthurralt; A/Prof Shilpi Ajwani; Professor Carolyn Day (Elsevier, 2023)
Aim or Purpose: To assess Sydney Dental Hospital (SDH) clinicians' beliefs, attitudes, and experience in identification and response to domestic violence (DV) in a public dental setting prior to the implementation of Domestic Violence Routine Screening (DVRS). Materials and Methods: An anonymous cross-sectional survey was conducted amongst SDH clinicians from one general and two specialist clinics between November and December 2022 following completion of DVRS training and prior to DVRS implementation. The survey consisted of 10 questions addressing clinicians' characteristics (demographic and educational history), their knowledge, perception, and previous experience responding to women disclosing DV. The study was approved by RPAH Ethics Committee. Results: Thirty-two clinicians participated (73% response), with 56% aged 25-34, 47% with more than 10 years of clinical experience (32% 5-10 years and 22% less 5 years) and 60% were general dentists. Most participants (75%) reported they had previously managed DV disclosures, and 63% agreed that responding to DV disclosure was part of their role, but 79% were not at all or only slightly confident in responding to DV disclosure prior to DVRS training. Nearly 60% considered that more training was needed, and their concerns included dealing with an ambiguous situation (95%), engaging with women to complete the screening (79%), responding to DV disclosures (79%) and child protection mandatory reporter requirements (63%). Conclusions: A large proportion of clinicians had previously managed DV disclosure prior to DVRS implementation and agreed that screening was part of their role but identified the need for more targeted training and support to increase their confidence in responding to DV and undertake DVRS.